Different Feathers Embedding Together: Integrating Diversity and Organizational Embeddedness - Ghosh, Debjani; Gonzalez, Jorge A.; Sekiguchi, Tomoki (Journal of Management Studies, 2024)
AbstractDespite the increase of demographic diversity in organizational environments, little is known about how and why employees from distinct demographic backgrounds (e.g., gender, race, and/or ethnicity) become embedded in their work organizations, which is a reason why employees stay and perform in their jobs. To address this research gap, we integrate job embeddedness and social identification/self‐categorization theories and draw from critical diversity studies to theorize on the effects of varying degrees of demographic diversity on the organizational embeddedness of diverse talent. Specifically, we theorize on how monolithic, pluralistic, and multicultural organizational stages, reflecting distinct degrees of heterogeneity, structural integration, and inclusion, affect the process by which employees from both dominant and marginalized social groups develop organizational embeddedness dimensions – links, fit, and sacrifice – with a distinct nature, order, degree, and speed. We further theorize how inclusive leadership can promote organizational embeddedness of employees from all social groups in the three organizational demography stages.